A lipid fusion based method for the single molecule study of ATP synthase - Russell, A; Aidan Russell (2014)
ATP synthase is a ubiquitous transmembrane protein that utilises the free energy available from ion gradients across lipid membranes to synthesise adenosine triphosphate (ATP). It may be separated into two parts - the membrane-embedded (i.e. hydrophobic) FO and the hydrophilic F1. Each undergoes a rotary motion. Single-molecule studies on the rotation of the isolated hydrophilic F1 have been performed for many years; attempts to construct an experiment in which to view the rotation of the membrane-embedded F1FO complex under high space- and time- resolution (such as by attachment of a rotational probe) have not yet seen a satisfactory method emerge in the literature. Most particularly, a clear ability to generate and control a proton-motive force across the membrane in which the F1FO is sited is needed to probe ATP synthesis. This thesis presents the development of a candidate method for such single-molecule studies. By the use of a water-in-oil emulsion, giant unilamellar lipid vesicles are formed which entrap arbitrary components - including functionalised gold nanospheres of 60-100 nm diameter, which move freely in the internal space. A charge-based lipid fusion is developed, using mixtures of natural lipid extracts with anionic and cationic lipids. It is demonstrated that anionic giant vesicles fuse with cationic small vesicles with full content mixing and transfer of bilayer leaflets. It is shown that F1FO is functional in the cationic lipid mixture. Methods are shown to bind such a cationic proteoliposome to a surface and for it to fuse with an anionic giant vesicle containing functionalised gold nanospheres. Backscatter laser darkfield is used to search for rotation of the gold nanospheres under ATP hydrolysis conditions of the F1FO; unidirectional rotation is seen in one instance and other suggestive traces are shown with speculative analysis. Further work is proposed.